Hüseyin Vaiz-i Kâşifi ve mevâkib tefsiri - Aldemir, Merve (My University, 2019)
Müslüman toplumların İslam tasavvuru ve din anlayışı en iyi bir şekilde Kur’ân’a bakış açılarından ve toplum içerisinde yazılan tefsir kitaplarından okunabilir. Osmanlı döneminde medreselerde ilmî tartışmaların da bolca yer aldığı Arapça tefsirler ağırlıklı olarak kullanılırken; halkın rivâyet ve tasavvufî yorumlarıyla ön plana çıkan, ‘avâmî’ bir üslûpla yazılan tefsirleri okuduğu görülmektedir. İsmâil Ferruh Efendi’nin avamın anlaması amacıyla mümkün mertebe sade ve anlaşılır bir üslûpla kaleme aldığı Mevâkib Tefsiri, Tibyan’la birlikte Osmanlı’da en çok basılan ve okunan tefsirler arasındadır. Osmanlı tefsir ve Kur’ân tercümeleri geleneği hakkında bilgi edinmemiz açısından önemli olan Mevâkib Tefsiri araştırmamızın temel konusunu oluşturur. Hüseyin Vâiz-i Kâşifî’ye ait Mevâhib-i Aliyye isimli Farsça tefsiri temel kaynak olarak kullandığı için Mevâkib Tercüme-i Tefsir-i Mevâhib olarak adlandırılırken, farklı muteber kaynaklardan da istifâde ettiği için müellifin Mevâhib’den hareketle yaptığı tercüme-tefsiri olarak da nitelendirilebilir.

The Islamic concept of Muslim societies and the understanding of religion can best be read from the Qur'anic perspectives and from the commentary books written in the community. While the Arabic tafsir, in which many scholarly disputes are included, is used in the madrasa in the Ottoman period, it can be seen that the public reads the commentaries written in a simple ‘avâmî’ style that comes to the forefront with is narration and mystical ‘sufis’ interpretations. The interpretation of Mevâkib, which Ferruh Efendi had written with a simple and understandable way in order to make sense of the meaning, was among the most widely published and read commentaries in the Ottoman Empire with Tibyan. Interpretation of the Mevâkib which is important in terms of gaining information about the tradition of Ottoman tafsir and Quran translations is the main subject of our research. While it is called Mevâkib Terceme-i Tefsir-i Mevâhib since Ferruh Efendi uses the Persian Tafsir Mevâhib-i Aliyye by Hüseyin Vâiz-i Kâşifî as the main source, it may be described as Mevâhib tafsir-commentary due to the fact that it also makes use of different reliable sources.
Keywords: Hermeneutics; İsmail Ferruh; İsmâil Ferruh; Kâşifî; Mevâkib; Tafsir; Tefsir - Tercüme; Tefsir bilimi; Translation